Distribusi Zakat bagi Perempuan dan Anak Korban Kekerasan menurut Tokoh MUI Kabupaten Ponorogo - Atik Husnia Mabruroh; Ahmad Junaidi (Fakultas Syariah Institut Agama Islam Negeri Ponorogo, 2023)
This study aims to explain how the views and the basis of thinking of MUI figures Ponorogo Regency in determining the law of women and children as mustahik zakat. This research is qualitative research with field research and a descriptive qualitative approach. While data collection techniques by conducting interviews and documentation. The analysis used in this research is descriptive analysis with an inductive method. The results of this study can be concluded that (1) Most MUI figures in Ponorogo Regency stated that the words